Acetogenic production of 3-Hydroxybutyrate using a native 3-Hydroxybutyryl-CoA Dehydrogenase - Lo, Jonathan; Humphreys, Jonathan R.; Magnusson, Lauren; Wachter, Benton; Urban, Chris; Hebdon, Skyler D.; Xiong, Wei; Chou, Katherine J.; Ching Maness, Pin (Frontiers in Microbiology, 2022)
3-Hydroxybutyrate (3HB) is a product of interest as it is a precursor to the commercially produced bioplastic polyhydroxybutyrate. It can also serve as a platform for fine chemicals, medicines, and biofuels, making it a value-added product and feedstock. Acetogens non-photosynthetically fix CO2 into acetyl-CoA and have been previously engineered to convert acetyl-CoA into 3HB. However, as acetogen metabolism is poorly understood, those engineering efforts have had varying levels of success. 3HB, using acetyl-CoA as a precursor, can be synthesized by a variety of different pathways. Here we systematically compare various pathways to produce 3HB in acetogens and discover a native (S)-3-hydroxybutyrate-CoA dehydrogenase, hbd2, responsible for endogenous 3HB production. In conjunction with the heterologous thiolase atoB and CoA transferase ctfAB, hbd2 overexpression improves yields of 3HB on both sugar and syngas (CO/H2/CO2), outperforming the other tested pathways. These results uncovered a previously unknown 3HB production pathway, inform data from prior metabolic engineering efforts, and have implications for future physiological and biotechnological anaerobic research.